Transferrin variation and genetic structure of reindeer populations in Scandinavia - Røed, Knut H.; Mossing, T.; Nieminen, M.; Rydberg, A. (Rangifer, 1987)
Polyacrylamide gel electrophoresis was used to analyse transferrin variation in herds of semi-domestic reindeer from Scandinavia. The results are compared with previously reported values for other populations of both semi-domestic and wild reindeer using the same techniques as in the present study. In all populations the number of alleles was high, ranging from seven to eleven, and the heterozygosity was correspondingly high, with a mean of 0.749. This high genetic variation in all populations suggests that inbreeding is not widespread among Scandinavian reindeer. The pattern of allele frequency distribution indicates a high degree of genetic heterogeneity in the transferrin locus, both between the different semi-domestic herds and between the different wild populations. The mean value of genetic distance was 0.069 between semi-domestic herds and 0.091 between wild populations. Between semi-domestic and wild populations the genetic distance was particularly high, with a mean of 0.188. This high value was mainly due to a different pattern in the distribution of the two most common transferrin alleles: Tfu was most common among semi-domestic herds, while TfEI was most common among wild populations. These differences in transferrin allele distribution are discussed in relation to possible different origins of semi-domestic and wild reindeer in Scandinavia, or alternatively, to different selection forces acting on transferrin genotypes in semi-domestic and wild populations. Transferrin-variasjon og genetisk struktur hos rein i Skandinavia. Abstact in Norwegian / Sammendrag: Transferrin-variasjon i tamreinflokker ble analysert ved hjelp av polyacrylamid gel elektroforese. Resultatene er sammenlignet med verdier som tidligere er beskrevet for både tamrein og villrein hvor det ble benyttet samme metode som i denne undersøkelsen. I alle populasjonene ble det registrert et høyt antall alleler (7-11) og heterozygositeten var tilsvarende høy med en middelverdi på 0.749. Denne høye graden av genetisk variasjon i alle undersøkte populasjoner indikerer at det ikke foregår mye innavl blant rein i Skandinavia. Utbredelsen av de enkelte allelene viste høy grad av genetisk oppdeling i transferrin-locuset mellom flokker av både tamrein og villrein. Middelverdien for genetisk avstand var 0.069 mellom tamreinflokker og 0.091 mellom villreinflokker. Særlig stor genetisk avstand (middelverdi 0.188) ble funnet mellom tamrein og villrein. Denne store forskjellen skyldes i stor grad forskjellig mønster i utbredelsen av de to vanligste allelene: Tf' var mest vanlig blant tamrein og Tf1' var mest vanlig blant villrein. Denne forskjellen er diskutert i relasjon til forskjellig opprinnelse av tamrein og villrein og alternativt, i relasjon til forskjellig seleksjonskrefter som virker på transferrin genotyper i tamrein og villrein.